Early experience in ureteroscopy for the management of ureteric stone - Agarwal, A; Shrestha, P; Belokar, WK (Journal of College of Medical Sciences-Nepal, 2012)
Ureteroscopy has revolunized the management of ureteric calculus and it has become the need of every urology center today. The purpose of this study is to report our experience and results in the management of ureteric calculus by semi-rigid ureteroscopy and pneumatic lithotripsy and also to access the safety of procedure in untrained hands. Retrospective analysis of 48 consecutive patients of ureteric calculus treated by semi-rigid ureteroscopy and pneumatic lithotripsy between June 2010 and October 2010 in urology unit, College of Medical Sciences, Bharatpur, Nepal was done. 34 female patients (70.8%) and 14 male patients (29.2%) were identified. Mean age of female was 30.9years (range 17 to 45 years) and that of male was 46.4 years (range 33 to 63years). Mean stone size in female was 8.91mm (range 6.5 to 11.2mm) and in male it was 9.11mm (range 6 to 14.2mm). Lower ureteric calculus was present in 29 and 8(77.1%), mid ureteric calculus in 2 and 2(8.3%) and upper ureteric calculus in 3 and 4(14.6%) female and male patients respectively. Ureteric perforation occurred in 2 patients (4.2%). Ureteric avulsion occured in 1 female patient (2.1%) with upper ureteric calculus. DJ stent was keept in 34(70.8%) cases but in 11 cases (32.6%) DJ stent had to be removed earlier than 4 weeks due to stent related problems. Urine culture was sent before ureteroscopy in all the patients and was sterile in 24 patients (50%), contaminated growth in 12 patients (25%), grew E-coli in 8 patients (16.7%) and Kliebsella pneumonia in 2 patients(4.2%). Average duration of stay was 2.7 days. 5 patients developed fever post operatively, managed by intravenous antibiotics. There was no mortality. Though ureteroscopy has become a boon for the management of ureteric calculus, complications like perforation, ureteric avulsion, residual stone and stone migration are more in upper ureteric calculus and stone size > 1cm. Stenosed ureteral assess can be made with proper guide wire selection and prior dilatation .The procedure is relatively safe even in inexperienced hands. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 28-33 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6738